The Role Of Room Attendants In Increasing The Comfort Quality Of Guest Rooms At Artotel Gajahmada Hotel Semarang - Ganjar Hergiandari; Dedi Joko Purnomo (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Ganjar Hergiandari C13.2019.00270. 2023. The Role of Room Attendants Improving the Quality of guest room comfort at the Artotel Gajahmada Semarang Hotel. Hospitality Management Applied Undergraduate Study Program, Faculty of Cultural Sciences, Dian Nuswantoro University.This final project aims to explain the role of a Room Attendant, especially in the Housekeeping department in supporting operations. A Room Attendant has duties and responsibilities in working on guest rooms, by providing the best quality of room comfort for hotel guests at Artotel Gajahmada Semarang. This research is a research that uses a qualitative approach with a descriptive type. Data collection techniques using qualitative research methods for the data collection process are obtained through interviews, observation, and documentation, to obtain the correct data. The research results obtained show that the comfort of guest rooms is supported by three things, namely tidiness, beauty, and completeness. By implementing these three things, it will make guests feel comfortable and at home while staying at the hotel at Artotel Gajahmada Semarang.